Diagnostic exome sequencing in non-acquired focal epilepsies highlights a major role of GATOR1 complex genes. Issue 9 (21st February 2020) - Krenn, Martin; Wagner, Matias; Hotzy, Christoph; Graf, Elisabeth; Weber, Sandrina; Brunet, Theresa; Lorenz-Depiereux, Bettina; Kasprian, Gregor; Aull-Watschinger, Susanne; Pataraia, Ekaterina; Stogmann, Elisabeth; Zimprich, Alexander; et al.
Abstract : Background: The genetic architecture of non-acquired focal epilepsies (NAFEs) becomes increasingly unravelled using genome-wide sequencing datasets. However, it remains to be determined how this emerging knowledge can be translated into a diagnostic setting. To bridge this gap, we assessed the diagnostic outcomes of exome sequencing (ES) in NAFE. Methods: 112 deeply phenotyped patients with NAFE were included in the study. Diagnostic ES was performed, followed by a screen to detect variants of uncertain significance (VUSs) in 15 well-established focal epilepsy genes. Explorative gene prioritisation was used to identify possible novel candidate aetiologies with so far limited evidence for NAFE. Results: ES identified pathogenic or likely pathogenic (ie, diagnostic) variants in 13/112 patients (12%) in the genes DEPDC5, NPRL3, GABRG2, SCN1A, PCDH19 and STX1B . Two pathogenic variants were microdeletions involving NPRL3 and PCDH19 . Nine of the 13 diagnostic variants (69%) were found in genes of the GATOR1 complex, a potentially druggable target involved in the mammalian target of rapamycin (mTOR) signalling pathway. In addition, 17 VUSs in focal epilepsy genes and 6 rare variants in candidate genes ( MTOR, KCNA2, RBFOX1 and SCN3A ) were detected. Five patients with reported variants had double hits in different genes, suggesting a possible (oligogenic) role of multiple rare variants. Conclusion: This study underscores the molecular heterogeneity of NAFE with GATOR1 complex genes representing the by far most relevant genetic aetiology known to date. Although the diagnostic yield is lower compared with severe early-onset epilepsies, the high rate of VUSs and candidate variants suggests a further increase in future years.